Organic soluble and uniform film forming oligoethylene glycol substituted BODIPY small molecules with improved hole mobility - Singh, Saumya; Venugopalan, Vijay; Krishnamoorthy, Kothandam (Physical Chemistry Chemical Physics, 2014)
Judiciously chosen side chains of conjugated molecules have a positive impact on charge transport properties when used as the active material in organic electronic devices. Amongst the side chains, oligoethylene glycols (OEGs) have been relatively unexplored due to their hydrophilic nature. OEGs also affect the smooth film formation of conjugated molecules, which preclude device fabrication. However, X-ray diffraction studies have shown that OEGs facilitate intermolecular contact, which is a desirable property for the fabrication of organic electronic devices. Thus the challenge is to design and synthesize organic solvent soluble and uniform film forming conjugated molecules with OEG side chains. We have designed and synthesized conjugated small molecules (CSMs) comprising BODIPY as acceptor and triphenylamine as donor with an OEG side chain. This molecule forms smooth films when processed from organic solvents. In order to understand the impact of the OEG side chain, we have also synthesized alkyl chain analogs. All the molecules exhibit exactly the same HOMO and LUMO energy levels, but the packing in the solid state is different. CSM with methyl side chains exhibit an inter planar distance of 4.15 A. Contrary to this, the OEG side chain containing CSM showed an inter planar spacing of 4.30 A, which is 0.2 A less than the alkyl side chain comprising CSMs. Please note that the length of the hydrophobic and hydrophilic side chains is the same. Interestingly, the OEG side chain comprising CSM showed two orders of higher hole carrier mobilities compared to all the other derivatives. The same molecule also showed an extremely low threshold voltage of -0.27 V indicating the OEG side chains' favourable interaction between substrate as well as between molecules.

Synthesis, optoelectronic, and transistor properties of BODIPY- and cyclopenta[c]thiophene-containing pi-conjugated copolymers - Debnath, Sashi; Singh, Saumya; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (Journal of Physical Chemistry C, 2015)
Three new low-band-gap copolymers were synthesized by fusing dipyrromethene difluoroborane (BODIPY) as the acceptor (A) and thiophene-capped 5,5-bis(hexyloxymethyl)-5,6-dihydro-4H-cyclopenta[c]-thiophene (CPT) as the donor (D). The BODIPY unit was copolymerized through the `alpha' positions (1 and 7 positions) in P1 and through the `beta' positions (2 and 6 positions) in P2 and P3. The additional acetylene unit between D and A in P3 enhanced the conjugation by minimizing the possible steric hindrance compared to that in P2, whereas P1 exhibited a more red-shifted absorption than P2 and P3 because of the more effective conjugaion through the `alpha' positions of BODIPY. Importantly, the optical band gaps (E-g(opt)) obtained from the onset of the absorption spectra are 1.28, 1.71, and 1.57 eV for P1, P2, and P3, respectively. P1 has the lowest band gap for any CPT-containing polymer. In the best transistor devices, a mobility improvement by 4 orders of magnitude from 3.22 x 10(-6) cm(2) V-1 s(-1) for P2 to 0.01 cm(2) V-1 s(-1) for P1 was achieved. DFT calculations alongside measured charge-transport properties indicated that appreciable alterations in the optoelectronic properties of the polymers were achieved through minor changes in their structural features. The polymers were further characterized by thin-film X-ray diffraction, atomic force microscopy, and spectroelectrochemistry to investigate their material and electrochemical properties.

Copolymers comprising monomers with various dipole and quadrupole as active material in organic field effect transistors - Singh, Saumya; Chithiravel, Sundaresan; Krishnamoorthy, Kothandam (Journal of Physical Chemistry C, 2016)
Copolymers of 4,4-difluoro-4-borata-3a-azonia-4a-aza-s-indacene (BODIPY) and diketopyrrolopyrrole (DPP) were synthesized. The BODIPY has a permanent dipole and the DPP has a quadrupole. The dipole and the quadrupole in the monomers are expected to bring the polymers closer and to improve the charge-transport properties. By judicious choice of these monomers, the electron wave function is evenly distributed through the molecules. However, we notice that the torsional angle at the connecting point of BODIPY and DPP is a function of the methyl moieties at the beta,beta' position of the BODIPY. We found that the polymer comprising DPP and BODIPY without methyl moiety at beta,beta' position showed a torsional angle of 27, the lowest among the three polymers studied in this work. The absorption spectrum of the polymer showed transitions because of vibronic coupling indicating linearity along the polymer backbone. The band gap of the polymer was found to be 1.2 eV. The thermally stable polymer showed an ambipolar charge transport of 0.01 cm(2)/(V s).

Site-selective synthesis and characterization of BODIPY-acetylene copolymers and their transistor properties - Debnath, Sashi; Singh, Saumya; Bedi, Anjan; Krishnamoorthy, Kothandam; Zade, Sanjio S. (Journal of Polymer Science Part A-Polymer Chemistry, 2016)
To study the effect of site-selective copolymerization of borondipyrromethene (BODIPY) with acetylene on the structural and optoelectronic properties, three copolymers P1-P3 were synthesized by the Sonogashira cross-coupling of BODIPY units with diacetylene and bromine capping through all the possible linkages: alpha-alpha (P1), alpha-beta (P2), and beta-beta (P3). The optoelectronic properties of the polymers were investigated systematically to understand the effect of site-selective polymerization. The HOMO levels of the polymers were significantly tuned from P1 to P3 with negligible change in the LUMO levels. Broadening of absorption spectra from P3 to P1 was observed because of increase in the extent of conjugation. Additionally, the charge transport properties of these polymers in organic thin-film transistors (OTFTs) revealed that P1 and P3 exhibited only p-type mobility, whereas P2 exhibited electron mobility. Notably, the further investigations of the surface morphology of polymer films by atomic force microscopy (AFM) unveiled that comb like nanostructural arrangements in P3 was beneficial for the charge-carrier mobility over the circular arrangements in P1 and P2. (C) 2016 Wiley Periodicals, Inc.
Keywords: acetylene; BODIPY; DFT; low-band gap

Modulated photochemical reactivities of O-acetylated (3', 5'-dimethoxyphenyl) heteroaryl acyloin derivatives under direct irradiation and photo-induced electron transfer conditions - Bisht, Rajesh; Singh, Saumya; Krishnamoorthy, Kothandam; Nithyanandhan, Jayaraj (Photochemical & Photobiological Sciences, 2018)
3', 5'-Dimethoxybenzoin esters are important photoremovable protecting groups which form 2-phenylbenzofuran derivatives upon photo-release. We utilized a similar concept to test a photochemical method of installing a benzofuran moiety to the conjugated backbone by subjecting O-acetylated (3', 5'-dimethylphenyl) heteroaryl acyloin derivatives through direct photo irradiation and a photo-induced electron transfer reaction. These photochemical methods were explored for a variety of heteroaromatic substrates appended on the ketone part of the O-acetylated cross-acyloin derivatives. The furan, thiophene and bithiophene derivatives led to the expected cyclized (benzofuran capped) products but the derivatives with extended conjugation decomposed under direct irradiation. However, under irradiation in the presence of an electron donor such as triethylamine, the extended acyloin derivatives afforded both cyclized and deacetoxylated products. The semiconducting nature of the extended cyclized products was also explored and tested for solution-processed organic field effect transistors, providing a maximum hole mobility of 1.3 x 10(-6) cm(2) V-1 s(-1).